As pesquisas sobre o ensino da estatística e da probabilidade no período de 2000 a 2008: uma pesquisa a partir do banco de teses da CAPES - Ribeiro, Silverio Domingos (2010)
This study was aimed at collecting all the academic and scientific researches from the Capes Thesis bank, Such data referred to the studies related to the problems concerning the Statistics and Probability teaching; by taking into account the Masters and Phd s degrees which took place from 2000 to 2008. We have compiled fiftyeight researches from twenty-two universities located in the South, Southeast and Midwest of Brazil. Based on the summaries of such researches, we analyzed them and came up with five themes. Our aim is to present this academic and scientific study in a systematic way, in order to provide references for future researchers, concerning the Statistics and Probability teaching. Regarding each theme, we made a meta-analysis of the researches and we can point out that in the theme concerning the process of teaching and learning of Statistics and Probability there was the occurrence of a significant number of studies that used computers as a resource for the teaching of Statistics and Probability. In this thematic line we could also find studies that investigated what the implications of an approach by using the thematic modeling to promote a critical Mathematics were. According to the main theme on the initial and continuing training of teachers of mathematics, most studies were concerned about the attitudes, satisfaction and belief of the teachers in relation to the understanding of this issue. In the theme identified as the teaching practice, beliefs, conceptions and practical knowledge, a great number of researches focused their investigation on the issue of teaching Statistics and Probality at both elementary and high school. In this axis we feel that there is a lack of studies which investigate the use of computers in teaching practice and the effect of this approach in the belief of the teachers in relation to the study of Statistics and Probability. The main theme, about the usage of ICTs in Statistics teaching, investigated how the computer could become a facilitator for the teaching of such subject. Besides, the theme line distance learning (ODL) was investigated by two surveys. In the Theme about curriculum changes, most researches dealt with the issue of conceptual errors in textbooks and their influence in the classroom practice